ИНВЕРЗИЈАТА НА МАКЕДОНСКИОТ ЗЕМСКИ ГРБ ВО ИЛИРСКИОТ ГРБОВНИК И СТЕМАТОГРАФИИТЕ НА ВИТЕЗОВИЌ И ЖЕФАРОВИЌ - HE INVERSION OF THE MACEDONIAN LAND COAT OF ARMS IN THE ILLYRIAN ARMORIAL AND THE STEMMATOGRAPHIAS OF VITEZOVIC AND ZHEFAROVIC - Nacevski, Ivan (Македонски хералд - Macedonian Herald, 2020)
Heraldic inversion is the process of differentiating by switching the color of the shield and the color of the heraldic figure in order to obtain another, heraldically different coat of arms, but indicating a connection between them. From the very beginning of research on the Macedonian coat of arms, a similarity to the Bulgarian coat of arms has been observed and attempts have been made to explain their so-called inversion, which undoubtedly has entered as a significant point in the study of their development. We find the possible inversion of the Macedonian and Bulgarian coats of arms in Illyrian heraldry and it cannot be found outside this group. In fact, we do not find the two coats of arms together in any other older work except in the book Delle Imprese by Capaccio. Regarding the possible origins of the coats of arms of Macedonia and Bulgaria, basically two views stand out: the first is that coats of arms have a common source for the blazons, and the second is that coats of arms have two separate sources of blazons.